2018
DOI: 10.1002/cam4.1784
|View full text |Cite
|
Sign up to set email alerts
|

Prospective memory impairment following whole brain radiotherapy in patients with metastatic brain cancer

Abstract: ObjectiveTo investigate the prospective memory (PM) impairment following whole brain radiotherapy (WBRT) in cancer patients with brain metastases.MethodEighty‐one patients with metastatic brain cancer, agreeing to undergo WBRT, were enrolled and subjected to a battery of cognitive neuropsychological tests, including the mini‐mental state examination (MMSE), verbal fluency test (VFT), digit span test (DST), and event‐based and time‐based prospective memory (EBPM and TBPM) tasks, before and after radiotherapy.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…For the latter, Trifiletti et al showed a latency period of 10,2 months after WBI [11]. In contrast, Cheng et al reported early cognitive impairment at one month after WBI, likely due to the frontal lobe damage [12]. Between these opposing positions, Kepka et al [13] supported that the omission of WBI after post-operative SRS delivered to the tumor bed affected the quality of life (QoL) and survival rates due to a poor sub-clinical disease control.…”
Section: Introduction/rationalementioning
confidence: 98%
“…For the latter, Trifiletti et al showed a latency period of 10,2 months after WBI [11]. In contrast, Cheng et al reported early cognitive impairment at one month after WBI, likely due to the frontal lobe damage [12]. Between these opposing positions, Kepka et al [13] supported that the omission of WBI after post-operative SRS delivered to the tumor bed affected the quality of life (QoL) and survival rates due to a poor sub-clinical disease control.…”
Section: Introduction/rationalementioning
confidence: 98%
“…13 The most common and relevant adverse event related to WBRT is permanent neurocognitive impairment, which, in some cases, may outweigh its benefits. 14 Novel targeted therapies have improved CNS penetration and revealed potent intracerebral activity in patients with NSCLC with driver genes activating mutations and BM, even without previous RT. 15 Immunotherapy, alone or in combination with chemotherapy, is now the standard of care for first-line treatment of patients with NSCLC without an actionable driver mutation.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with a unique or a limited number of BM are considered eligible for treatment with complete surgical resection or stereotactic radiosurgery, and WBRT is preferably administered to patients with multiple BM ( 32 ). Complications following stereotactic radiosurgery such as radio necrosis and WBRT such as permanent neurocognitive impairment may outweigh the benefits ( 33 , 34 ). Therefore, RT sparing management has become increasingly attractive ( 35 ).…”
Section: Discussionmentioning
confidence: 99%